First-generation undergraduate researchers: understanding shared experiences through stories - Henrichsen, Christine M.; Keenan, Susan M. (Frontiers in Education, 2023)
If you want to know a person, you need to know their story. If institutions want to better support their students, they need to know them and therefore need to know their stories. First-generation students—a vital part of our academic communities—model qualities such as hard work, optimism, and perseverance. Academic settings, policies, and hidden curricula present challenges for first-generation students and often result in inequitable outcomes. Undergraduate research experiences (UREs) are one of the resource institutions that have to support these students. Little is known about the first-generation student experience in UREs. Using in-depth interviews, we collected the stories of first-generation biology students who had participated in UREs. A thematic analysis illuminated five themes of shared experiences: what to expect in college, parental support, intent to apply to medical school, mentorship, and becoming a researcher. Stories provide depth and details into these themes that cannot be highlighted using other methodologies. We share detailed accounts of the experiences of two first-generation students. By using portions of the original conversations, the students narrate their stories in their own voices. A dialogical method was used to juxtapose the two stories and to increase opportunities for reader reflexivity and introspection. We discuss how the stories relate to the literature and reflect on the power of that gathering and sharing stories of first-generation students' experiences.